KARONESE CODE SWITCHING IN CULTURAL ADJUSTMENT PROCESS AMONG SMAN1 PANCUR BATU SENIOR HIGH SCHOOLS STUDENTS - Jeffri Nando Karo Karo; Mayasari .; Zuindra .; Wan Anayati; Muhammad Kiki Wardana (Jurnal Education and Development, 2021)
Code-switching is a part of sociolinguistic occurring in conversation and writing. Study of code switching has two approaches: grammatical and sociolinguistic perspective and the present study includes the sociolinguistic perspective. The study used a descriptive qualitative design to describe the types of code switching in bilingual teaching classroom interactions, and the functions of code switching used by the Karonese students in cultural adjustment process. The result of the study showed that there were three main types of code switching uttered by Karonese students in cultural adjustment process through classroom discussion. They are intersentential, intra sentential and tag switching. The main reason of using code switching is to increase in variety of words and sentences used in classroom discussion. The function of code switching used by Karonese students in cultural adjustment process is to enrich the vocabulary of English, Indonesian and Karonese in classroom discussion.